Chalcone and cinnamate synthesis via one-pot enol silane formation-Mukaiyama aldol reactions of ketones and acetate esters. Issue 32 (8th August 2018) - Downey, C. Wade; Glist, Hadleigh M.; Takashima, Anna; Bottum, Samuel R.; Dixon, Grant J.
Graphical abstract: Highlights: Unsaturated carbonyls are produced from reaction of ketones or esters with aldehydes. Stoichiometry of trimethylsilyl trifluoromethanesulfonate determines reaction outcome. Electron-poor aldehydes do not lead to elimination products. Abstract: Aryl alkyl ketones, acetate esters, and acetamides undergo facile one-pot enol silane formation, Mukaiyama aldol addition, and dehydrosilyloxylation in the presence of an amine base and excess trimethylsilyl trifluoromethanesulfonate. The chalcone and cinnamate products are generally recovered in high yield. The relative stoichiometry of the trimethylsilyl trifluoromethanesulfonate and amine base reagents determines whether the reaction yields the β-silyloxy carbonyl product or the α, β-unsaturated carbonyl.